3D Structure and Interaction of p24β and p24δ Golgi Dynamics Domains: Implication for p24 Complex Formation and Cargo Transport. Issue 20 (9th October 2016) - Nagae, Masamichi; Hirata, Tetsuya; Morita-Matsumoto, Kana; Theiler, Romina; Fujita, Morihisa; Kinoshita, Taroh; Yamaguchi, Yoshiki
Abstract: The p24 family consists of four subfamilies (p24α, p24β, p24γ, and p24δ), and the proteins are thought to form hetero-oligomeric complexes for efficient transport of cargo proteins from the endoplasmic reticulum to the Golgi apparatus. The proteins possess a conserved luminal Golgi dynamics (GOLD) domain, whose functions are largely unknown. Here, we present structural and biochemical studies of p24β1 and p24δ1 GOLD domains. Use of GOLD domain-deleted mutants revealed that the GOLD domain of p24δ1 is required for proper p24 hetero-oligomeric complex formation and efficient transport of GPI-anchored proteins. The p24β1 and p24δ1 GOLD domains share a common β-sandwich fold with a characteristic intrasheet disulfide bond. The GOLD domain of p24δ1 crystallized as dimers, allowing the analysis of a homophilic interaction site. Surface plasmon resonance and solution NMR analyses revealed that p24β1 and p24δ1 GOLD domains interact weakly ( K d = 10 − 4 M). Bi-protein titration provided interaction site maps. We propose that the heterophilic interaction of p24 GOLD domains contributes to the formation of the p24 hetero-oligomeric complex and to efficient cargo transport. Graphical Abstract: Highlights: p24 family proteins are involved in intracellular protein transport. p24δ1 GOLD domain is essential for efficient transport of glycosylphosphatidylinositol-anchored proteins. p24β1 and p24δ1 GOLD domains have a β-sandwich fold with an intrasheet disulfide bridge. p24β1 and p24δ1 GOLD domains interact weakly. Interaction of GOLD domains may contribute to p24 hetero-oligomeric complex formation.